Barriers and facilitators of messaging platforms as a means of maternal support and care in rural communities: A systematic review - Shahreen Rahman; Asua Okolie; Dianne Bryant; Edward Kwabena Ameyaw; Obidimma Ezezika (PLoS ONE, 2025)
Improving maternal support in rural communities through messaging platforms can be a crucial strategy for enhancing antenatal visit rates and improving maternal health outcomes. Currently, there is a significant gap in maternal healthcare access in rural areas, where pregnant women often face barriers such as distance to healthcare facilities, lack of healthcare providers, and limited access to educational resources. This review explored the barriers and facilitators to providing maternal support through messaging platforms. A protocol for this systematic review was developed and registered in the PROSPERO international prospective register of systematic reviews database (Registration number: CRD42023492705). A comprehensive search was conducted on OVID MEDLINE, OVID EMBASE, EBSCO CINAHL, and SCOPUS, focusing on primary research articles published between January 1, 2003, and January 30, 2025. Eligibility criteria required studies to report on maternal support utilizing messaging platforms in rural populations globally. The search strategy yielded a total of 665 studies, of which 15 studies met the eligibility criteria. The quality of eligible studies was evaluated using the Mixed Methods Appraisal Tool, and data were extracted from the articles and analyzed using the Consolidated Framework for Implementation Research. Evidence from the studies indicated that messaging interventions positively impacted maternal health knowledge, access to perinatal services, and communication. Significant barriers were identified, including network connectivity issues in rural areas, affordability of airtime and phones, storage capacity of phones, resistance based on religious beliefs, reliance on traditional birth attendants, and literacy challenges. Facilitators in the messaging interventions included the educational nature of the messages, tailored advice related to pregnancy stages, timely support from community health workers, and improved access to transport for healthcare visits. Tailoring interventions to specific community needs and incorporating educational elements can enhance the engagement and success of messaging platforms targeting maternal health. The identified barriers and facilitators can inform the effective use of messaging platforms by ensuring they are accessible, affordable, and culturally appropriate to support maternal health in rural communities. Trial registration PROSPERO international prospective register of systematic reviews database (Registration number: CRD42023492705).